Use of the SWOT Analysis in the Field of National Security Planning - Artem Bratko; Dmytro Oleshko; Anton Datskov; Valerii Vychavka; Oleksandr Olytskyi; Ihor Balytskyi (Emerging Science Journal, 2021)
The authors propose to improve the methodology of operational and service activities planning based on the methodology of defense planning within the national security system on the basis of opportunities. The capability-based planning will allow for better planning of operational and service activities of the border agency and will ensure active cooperation between Ukraine and NATO in order to achieve the criteria necessary for full membership in the Alliance. A defense survey is conducted to assess the state and readiness of the defense forces to perform tasks related to the defense of Ukraine, the state of their personnel, financial, logistical and other types of support in the current and projected conditions of the security environment. The survey of the State Border Guard Service of Ukraine was conducted using an analytical method, namely the analysis of strengths and weaknesses, opportunities and threats (SWOT-analysis), which allows substantiating the main directions of the Development Strategy of the State Border Guard Service of Ukraine and increasing the level of operational and service activities planning within the system of national security. The State Border Guard Service of Ukraine is a component of the security and defense sector and the new conditions the border agency operates in arise the issue on improving the methodology of planning its operational and service activities. Doi: 10.28991/esj-2021-01280 Full Text: PDF